L’intervention ergonomique : que fait-on des caractéristiques personnelles comme le sexe et le genre ? - Nicole Vézina; Céline Chatigny; Bénédicte Calvet (Perspectives Interdisciplinaires sur le Travail et la Santé)
The development of interventions in ergonomics in the French-speaking world has opened up an important field of knowledge about how our practice is conducted. In recent years however, aside from the question of age, little has been done in ergonomic interventions to take into consideration personal characteristics such as sex and gender. Relying on a model of the steps involved in an ergonomic intervention, we identify at each step possible issues, questions, and avenues for research and action. We reflect on the knowledge – be it currently available or lacking – that is needed to intervene properly when sex and gender questions are posed. We suggest the development of intervention strategies to recognize and avoid the exclusion of female workers when it comes time to prioritize working situations or to organize participation groups. The concept of operational leeway is used to better understand the differentiated, sex-and-gender-based impacts that working conditions have on men’s and women’s capacity to stay healthy at work.